2023
DOI: 10.3390/s23084015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of the Coracohumeral Ligament Using Ultra-Sonography in Shoulder Contracture

Abstract: The coracohumeral ligament (CHL) is related to the range of motion of the shoulder joint. The evaluation of the CHL using ultrasonography (US) has been reported on the elastic modulus and thickness of the CHL, but no dynamic evaluation method has been established. We aimed to quantify the movement of the CHL by applying Particle Image Velocimetry (PIV), a technique used in the field of fluid engineering, to cases of shoulder contracture using the US. The subjects were eight patients, with 16 shoulders. The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previous reports have shown ICCs of 0.810 for humeral head translation in patients with shoulder instability 9 and 0.80 for the velocity of coracohumeral ligament in patients with frozen shoulder. 11 Therefore, the measurement method employed in the present study was capable of accurately calculating humeral head translation and ISP velocity. Furthermore, the differences observed between the throwing and nonthrowing sides were approximately 2.5 mm for D AT and approximately 0.20 mm/s for the mean ISP velocity during IR.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Previous reports have shown ICCs of 0.810 for humeral head translation in patients with shoulder instability 9 and 0.80 for the velocity of coracohumeral ligament in patients with frozen shoulder. 11 Therefore, the measurement method employed in the present study was capable of accurately calculating humeral head translation and ISP velocity. Furthermore, the differences observed between the throwing and nonthrowing sides were approximately 2.5 mm for D AT and approximately 0.20 mm/s for the mean ISP velocity during IR.…”
Section: Discussionmentioning
confidence: 89%
“…To determine the sample size, a power analysis was conducted using G∗Power 3.1.9 (Heinrich Heine Universität, Düsseldorf, Germany) based on a previous report that analyzed the velocity of soft tissue in the shoulder using PIV and compared both sides. 11 Sample size calculations indicated that a sample size of 12 participants would be sufficient to detect differences using a t test (effect size, d = 0.8; significance level, α = 0.05; power, 0.8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations